Aggregation of high‐frequency RBD mutations of SARS‐CoV‐2 with three VOCs did not cause significant antigenic drift. Issue 5 (28th January 2022) - Li, Tao; Cui, Zhimin; Jia, Yunfei; Liang, Ziteng; Nie, Jianhui; Zhang, Li; Wang, Meng; Li, Qianqian; Wu, Jiajing; Xu, Nan; Liu, Shuo; Li, Xueli; et al.
Abstract: Variants of SARS‐CoV‐2 continue to emerge, posing great challenges in outbreak prevention and control. It is important to understand in advance the impact of possible variants of concern (VOCs) on infectivity and antigenicity. Here, we constructed one or more of the 15 high‐frequency naturally occurring amino acid changes in the receptor‐binding domain (RBD) of Alpha, Beta, and Gamma variants. A single mutant of A520S, V367F, and S494P in the above three VOCs enhanced infectivity in ACE2‐overexpressing 293T cells of different species, LLC‐MK2 and Vero cells. Aggregation of multiple RBD mutations significantly reduces the infectivity of the possible three VOCs. Regarding neutralization, it is noteworthy that E484K, N501Y, K417N, and N439K predispose to monoclonal antibodies (mAbs) protection failure in the 15 high‐frequency mutations. Most importantly, almost all possible VOCs (single RBD mutation or aggregation of multiple mutations) showed no more than a fourfold decrease in neutralizing activity with convalescent sera, vaccine sera, and immune sera of guinea pigs with different immunogens, and no significant antigenic drift was formed. In conclusion, our pseudovirus results could reduce the concern that the aggregation of multiple high‐frequency mutations in the RBD of the spike protein of the three VOCs would lead to severe antigenic drift, and this would provide value for vaccine development strategies. Highlights: Infectivity increased by adding three VOCs of V367F, S494P, or A520S. The infectivity of the three VOCs with multiple high‐frequency mutations decreased. Almost all of the possible variants of the three VOCs did not show severe antigenic drift.